Early strength agent for large-temperature-difference well cementation cement slurry and preparation method of early strength agent

The early strength agent for cement slurry with nano quartz and nano calcined kaolin addresses slow strength development in large temperature differences, enhancing cementing quality and safety in deep wells.

CN119118564AActive Publication Date: 2024-12-13JIAHUA SPECIAL CEMENT
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411268410.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

Existing technologies fail to address the issues of slow strength development in cement slurry with large temperature differences, leading to poor cementing quality and safety risks in deep and ultra-deep wells.

Method used

An early strength agent comprising nano quartz powder, nano calcined kaolin, and a dispersant, modified with a silane coupling agent, to enhance hydration and strength development in cement slurry under large temperature variations.

Benefits of technology

The agent promotes rapid strength development in low-temperature areas without affecting high-temperature thickening times, ensuring stable cementing quality and safety in long sealing sections.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118564A_ABST
    Figure CN119118564A_ABST
Patent Text Reader

Abstract

The invention discloses an early strength agent for large-temperature-difference well cementation cement slurry and a preparation method of the early strength agent. The early strength agent comprises the following components in parts by weight: 40-60 parts of nano quartz powder; 32 to 45 parts of nano calcined kaolin; 5-10 parts of a dispersant; and 3-5 parts of a silane coupling agent. When the early strength agent is prepared, the dispersing agent and the silane coupling agent are adopted to perform surface modification on the nano quartz powder and the nano calcined kaolin, so that the problem of slow strength development of large-temperature-difference well cementation cement paste in a low-temperature region section is solved, the well cementation quality of a long cementation section is guaranteed, and efficient and safe exploitation of deep oil and gas resources is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas well cementing, and in particular to an early strength agent for large temperature difference cementing slurry and a preparation method thereof. Background Art

[0002] With the continuous development of the domestic economy, the demand for oil and gas resources has continued to increase, the easily recoverable shallow oil and gas resources have continued to decrease, and oil field exploration and development has moved towards deep strata.

[0003] With the increase in the number of deep wells and ultra-deep wells, the number of cementing wells with long sealing sections is increasing. At present, cementing wells with long sealing sections mainly adopt one-time cementing technology, which faces the problems of long one-time return sealing section, large temperature difference between the top and bottom of the sealing section (>90℃), and super-slow setting of cement slurry at the top. These problems not only seriously affect the cementing quality, delay the progress of drilling operations, but also increase the safety risks of subsequent drilling operations. In the long sealing section of deep wells and ultra-deep wells, the static temperature at the bottom of the well can reach more than 150℃, and the temperature difference with the top of the well can reach more than 90℃. Due to the large temperature difference between the top and the bottom, the cement slurry pumping will go through a process from low temperature to high temperature and then to low temperature. In order to ensure the safe construction time of cementing wells with long sealing sections, high-temperature retarders are usually added to extend the pumping time of cement slurry. However, under the action of high-temperature retarders, the low-temperature section at the top of the cement slurry column is prone to slow setting or super-slow setting, and the slow development of cement slurry strength affects or even does not set, thus affecting the construction progress, efficiency and cementing quality. Improving cementing technology cannot fundamentally solve the problem of long-seal cementing with large temperature difference. Therefore, developing excellent admixtures suitable for large temperature difference cementing is an effective measure to solve the problem of long-seal cementing with large temperature difference.

[0004] At present, the main solution to the problem of super slow setting of top cement slurry during cementing of long sealing sections is to develop high-temperature and large temperature difference retarders. However, the existing high-temperature and large temperature difference retarders still have many difficult to solve problems, such as: sensitive dosage, unstable retarding effect, serious sedimentation of high-temperature cement slurry, poor matching with high-temperature admixtures, and easy to cause abnormal gelation, which is specifically manifested in the high-temperature thickening curve. The problem of slow strength development of large temperature difference cementing slurry in the low temperature area can also be solved by adding early strength agents for oil well cement. At present, the early strength agents used in oil well cement are mainly the following: (1) Inorganic salts: mainly chlorides, sulfates, carbonates, nitrates, nitrites and other inorganic substances; (2) Organics: mainly calcium formate, formamide, alcoholamine and other organic substances; (3) Nanomaterials: mainly nano-silicon dioxide, nano-calcium carbonate and other materials; (3) Composite early strength agents: the above early strength agents are compounded in proportion.

[0005] However, the oil well cement early strength agent of the prior art is not suitable for cement slurry with large temperature difference. There are the following problems: (1) The existing inorganic salt early strength agent has a great influence on the high temperature thickening time of cement slurry and has a significant high temperature accelerating effect, which easily leads to a shortening of the high temperature thickening time of cement slurry and is difficult to adjust by increasing the dosage of retarder. In addition, it may cause abnormal gelation of cement slurry, resulting in "core" and other phenomena in the cement thickening process, which is manifested as violent fluctuations in the thickening curve, forming "bulges" or "steps", and thus leading to poor cementing quality; (2) The dosage of existing organic early strength agents is relatively sensitive. When the admixture is small, the early strength effect is not obvious. Excessive dosage can easily lead to transitional slow setting of cement slurry and poor matching with high-temperature admixtures; (3) Due to the nano size, high surface energy and a large number of polar hydroxyl groups on the surface of existing nanomaterial early strength agents, they are easy to aggregate together in water and form large aggregates. They cannot be evenly dispersed in the cement slurry and it is difficult to effectively exert the nucleation effect, resulting in poor early strength effect; (4) The compound early strength agent is difficult to prepare and is difficult to apply to cement slurry systems with large temperature differences.

[0006] In view of the above problems, the present invention provides an early strength agent for large temperature difference cementing slurry to solve the problem that the existing large temperature difference cementing slurry has slow strength development at the top of the well, which affects the construction progress and cementing quality. Summary of the invention

[0007] The purpose of the present invention is to provide an early strength agent for large temperature difference cementing slurry and a preparation method thereof, so as to reduce the problem of slow strength development of temperature difference cementing slurry in low temperature area, thereby ensuring the cementing quality of long sealing section and ensuring efficient and safe exploitation of deep oil and gas resources.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0009] The present invention provides an early strength agent for large temperature difference cementing slurry, comprising the following components in parts by weight:

[0010] 40-60 parts of nano quartz powder;

[0011] 32-45 parts of nano calcined kaolin;

[0012] Dispersant 5-10 parts;

[0013] 3 to 5 parts of silane coupling agent.

[0014] In some embodiments of the present invention, the SiO2 content in the nano-quartz powder is ≥ 99.9wt%.

[0015] In some embodiments of the present invention, the particle size of the nano-quartz powder ranges from 300 to 400 nm.

[0016] In some embodiments of the present invention, the SiO2 content of the nano-calcined kaolin is ≥54wt%, the Al2O3 content is ≥32wt%, and the Fe2O3 content is <3wt%.

[0017] In some embodiments of the present invention, the particle size of the nano-calcined kaolin is in the range of 200 to 300 nm.

[0018] In some embodiments of the present invention, the dispersant is a polycarboxylic acid series high-efficiency water reducer, and the chemical composition is a modified polycarboxylate; the active ingredient in the modified polycarboxylate is ≥90%, and the molecular weight is between 10,000 and 30,000.

[0019] In some embodiments of the present invention, the silane coupling agent is one or more of KH550, KH560, KH570 and KH172.

[0020] In some embodiments of the present invention, the effective ingredient in the silane coupling agent is ≥ 98%.

[0021] The present invention also provides a method for preparing an early strength agent for large temperature difference cementing slurry, comprising the following steps:

[0022] Step 1, weighing 400-800 parts of anhydrous ethanol and 100-300 parts of deionized water by mass and mixing them thoroughly to obtain a first mixed solution; weighing 3-5 parts of a silane coupling agent, adding it to the first mixed solution, and obtaining a second mixed solution after ultrasonic dispersion for 1 hour; adjusting the pH value of the second mixed solution to 4-5 with anhydrous oxalic acid to obtain a third mixed solution, wherein the third mixed solution is a modified solution of nano-quartz powder and nano-calcined kaolin, and transferring the third mixed solution to a reactor equipped with a heating, stirring and condensing reflux device; preferably, the anhydrous ethanol is 600 parts and the deionized water is 200 parts;

[0023] Step 2, weighing 40 to 60 parts of nano-quartz powder, 32 to 45 parts of nano-calcined kaolin and 5 to 10 parts of a dispersant by mass and mixing them uniformly to obtain a mixture; and slowly adding the mixture to the third mixed solution to obtain a fourth mixed solution; opening the reflux device in the reactor, heating to 60° C., controlling the stirring speed to 400 to 500 r / min, reacting the fourth mixed solution for 3 hours, removing the reaction solution, and obtaining a fifth mixed solution;

[0024] Step 3, vacuum filter the fifth mixed liquid, wash the filtered product with anhydrous ethanol, and then vacuum dry the filtered product to obtain an early strength agent for large temperature difference cementing slurry; preferably, the vacuum drying temperature is 50° C. and the drying time is 6 hours.

[0025] The early strength agent for large temperature difference cementing slurry provided in the present invention comprises four components: nano quartz powder, nano calcined kaolin, dispersant and silane coupling agent. In order to avoid agglomeration of nano quartz powder and nano calcined kaolin and affect the early strength effect, the dispersant and silane coupling agent are used to modify the surface of nano quartz powder and nano calcined kaolin. Nano-quartz powder and nano-calcined kaolin basically do not react with cement hydration products at room temperature, but can react with CH (calcium hydroxide) generated by cement hydration at high temperature (>110°C) to generate nano-hydrated calcium silicate and nano-hydrated calcium aluminate. The above-mentioned hydration products can act as crystal seeds in cement slurry, form a large number of nucleation sites in cement slurry, promote the formation of crystal nuclei, effectively stimulate cement hydration reaction, and have basically no effect on the cement hydration induction period and the initial stage of hydration acceleration period, but can significantly improve the hydration rate of cement in the late stage of acceleration period, and its acceleration process has a self-catalytic effect, making the cement hydration products more dense and better cementing, thereby improving the early strength of cement, and having basically no effect on high-temperature thickening time. In addition, since the components of nano-hydrated calcium silicate and nano-hydrated calcium aluminate, the hydration products of nano-quartz powder and nano-metakaolin, are similar to those of cement hydration products, they have good matching properties with high-temperature admixtures of large temperature difference cementing slurry.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The early strength agent provided by the present invention has no obvious promoting effect on the hydration rate of the cement slurry in the early stage of the hydration reaction of the large temperature difference cementing, and the hydration induction period is basically unchanged. It mainly acts on the late stage of the cement hydration acceleration period, promoting the strength development of the cement hydration acceleration period, and thus has little effect on the high temperature thickening time.

[0028] The early strength agent of the present invention reacts with CH (calcium hydroxide) generated by cement hydration at high temperature to generate nanometer-scale calcium silicate hydrate and calcium aluminate hydrate. The nanometer-scale hydration products can play a good nucleus effect in cement slurry, accelerate the hydration rate of cement hydration in the late stage of acceleration period, promote the generation of calcium silicate hydrate and accelerate the growth of calcium vanadium, enhance the compactness and cementing ability of hydration products, thereby effectively promoting the strength development of large temperature difference cementing slurry in the low temperature area, and ensuring the early strength of the top low temperature section of the long sealing section large temperature difference cementing slurry.

[0029] (2) The effective components and hydration products of the early strength agent of the present invention are similar to the main mineral components and hydration products of the large temperature difference cementing slurry. Therefore, the early strength agent has good adaptability in the large temperature difference cementing slurry, and is well matched with the high temperature retarder, high temperature fluid loss reducer and other external additives. The cement slurry has excellent high temperature thickening performance and the thickening time is adjustable. In addition, there is no abnormal gelation in the large temperature difference cementing slurry, which is specifically manifested in that the high temperature thickening curve does not show abnormal phenomena such as "bulging" and "stepping".

[0030] (3) The preparation method of the early strength agent for large temperature difference cementing slurry of the present invention is simple, and its raw materials are widely available. When used in combination with high-temperature fluid loss reducing agent, large temperature difference retarder and other additives, a large temperature difference cementing slurry system with excellent comprehensive working performance such as good rheological properties, no free liquid, low water loss, good high-temperature sedimentation stability, and high early strength can be prepared, thereby ensuring the cementing quality of long sealing sections and promoting the efficient and safe exploitation of deep oil and gas resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a high temperature thickening curve of a large temperature difference cementing slurry mixed with the early strength agent of the present invention.

[0032] Figure 2 This is the high temperature thickening curve of the large temperature difference cementing slurry mixed with the existing early strength agent

[0033] Figure 3 It is the high temperature thickening curve of large temperature difference cementing slurry without any early strength agent. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The terms "first", "second", "third", "fourth" etc. in the present invention are used to distinguish different objects, rather than to describe a specific order.

[0035] In the embodiment of the present invention, the SiO2 content in the nano-quartz powder is ≥ 99.9wt%.

[0036] In the embodiment of the present invention, the particle size of the nano-quartz powder ranges from 300 to 400 nm.

[0037] In the embodiment of the present invention, the SiO2 content in the nano-calcined kaolin is ≥54wt%, the Al2O3 content is ≥32wt%, and the Fe2O3 content is <3wt%.

[0038] In the embodiment of the present invention, the particle size of the nano-calcined kaolin is in the range of 200 to 300 nm.

[0039] In the embodiment of the present invention, the dispersant is a polycarboxylic acid series high-efficiency water reducing agent, and the chemical composition is a modified polycarboxylate; the active ingredient in the modified polycarboxylate is ≥90%, and the molecular weight is between 10,000 and 30,000.

[0040] In the embodiment of the present invention, the silane coupling agent is one or more of KH550, KH560, KH570 and KH172.

[0041] In the embodiment of the present invention, the effective component in the silane coupling agent is ≥ 98%.

[0042] Example 1

[0043] As a preferred embodiment of the present invention, the early strength agent for large temperature difference cementing slurry disclosed in this embodiment has a specific composition as shown in Table 1.

[0044] Table 1 Example 1 Early Strength Agent Components

[0045] Component name Weight parts / parts Nano quartz powder 40 Nano calcined kaolin 45 Dispersants 10 Silane coupling agent 5

[0046] The preparation method of the early strength agent for large temperature difference cementing slurry disclosed in this embodiment is:

[0047] Step 1, weighing 600 parts of anhydrous ethanol and 200 parts of deionized water by mass and mixing them thoroughly to obtain a first mixed solution; weighing 5 parts of a silane coupling agent, adding it to the first mixed solution, and obtaining a second mixed solution after ultrasonic dispersion for 1 hour; adjusting the pH value of the second mixed solution to 4-5 with anhydrous oxalic acid to obtain a third mixed solution, wherein the third mixed solution is a modified solution of nano-quartz powder and nano-calcined kaolin, and transferring the third mixed solution to a reactor equipped with a heating, stirring and condensation reflux device;

[0048] Step 2, weighing 40 parts of nano-quartz powder, 45 parts of nano-calcined kaolin and 10 parts of dispersant by mass and mixing them uniformly to obtain a mixture; and slowly adding the mixture to the third mixed solution to obtain a fourth mixed solution; opening the reflux device in the reactor, heating to 60° C., controlling the stirring speed to 400-500 r / min, reacting the fourth mixed solution for 3 hours, removing the reaction solution, and obtaining a fifth mixed solution;

[0049] Step 3, vacuum filter the fifth mixed liquid, wash the filtered product with anhydrous ethanol, and then vacuum dry the filtered product at a drying temperature of 50° C. for 6 hours to obtain an early strength agent for large temperature difference cementing slurry.

[0050] Example 2

[0051] As a preferred embodiment of the present invention, the early strength agent for large temperature difference cementing slurry disclosed in this embodiment has a specific composition as shown in Table 2.

[0052] Table 2 Example 2 Early Strength Agent Components

[0053]

[0054]

[0055] The preparation method of the early strength agent for large temperature difference cementing slurry disclosed in this embodiment is:

[0056] Step 1, weighing 600 parts of anhydrous ethanol and 200 parts of deionized water by mass and mixing them thoroughly to obtain a first mixed solution; weighing 4 parts of a silane coupling agent, adding it to the first mixed solution, and obtaining a second mixed solution after ultrasonic dispersion for 1 hour; adjusting the pH value of the second mixed solution to 4-5 with anhydrous oxalic acid to obtain a third mixed solution, wherein the third mixed solution is a modified solution of nano-quartz powder and nano-calcined kaolin, and transferring the third mixed solution to a reactor equipped with a heating, stirring and condensation reflux device;

[0057] Step 2, weighing 50 parts of nano-quartz powder, 39 parts of nano-calcined kaolin and 7 parts of dispersant by mass and mixing them uniformly to obtain a mixture; and slowly adding the mixture to the third mixed solution to obtain a fourth mixed solution; opening the reflux device in the reactor, heating to 60° C., controlling the stirring speed to 400-500 r / min, reacting the fourth mixed solution for 3 hours, removing the reaction solution, and obtaining a fifth mixed solution;

[0058] Step 3, vacuum filter the fifth mixed liquid, wash the filtered product with anhydrous ethanol, and then vacuum dry the filtered product at a drying temperature of 50° C. for 6 hours to obtain an early strength agent for large temperature difference cementing slurry.

[0059] Example 3

[0060] As a preferred embodiment of the present invention, the early strength agent for large temperature difference cementing slurry disclosed in this embodiment has a specific composition as shown in Table 3.

[0061] Table 3 Example 3 Early Strength Agent Components

[0062] Component name Weight parts / parts Nano quartz powder 55 Nano calcined kaolin 35 Dispersants 6 Silane coupling agent 4

[0063] The preparation method of the early strength agent for large temperature difference cementing slurry disclosed in this embodiment is:

[0064] Step 1, weighing 600 parts of anhydrous ethanol and 200 parts of deionized water by mass and mixing them thoroughly to obtain a first mixed solution; weighing 4 parts of a silane coupling agent, adding it to the first mixed solution, and obtaining a second mixed solution after ultrasonic dispersion for 1 hour; adjusting the pH value of the second mixed solution to 4-5 with anhydrous oxalic acid to obtain a third mixed solution, wherein the third mixed solution is a modified solution of nano-quartz powder and nano-calcined kaolin, and transferring the third mixed solution to a reactor equipped with a heating, stirring and condensation reflux device;

[0065] Step 2, weighing 55 parts of nano-quartz powder, 35 parts of nano-calcined kaolin and 6 parts of dispersant by mass and mixing them uniformly to obtain a mixture; and slowly adding the mixture to the third mixed solution to obtain a fourth mixed solution; opening the reflux device in the reactor, heating to 60° C., controlling the stirring speed to 400-500 r / min, reacting the fourth mixed solution for 3 hours, removing the reaction solution, and obtaining a fifth mixed solution;

[0066] Step 3, vacuum filter the fifth mixed liquid, wash the filtered product with anhydrous ethanol, and then vacuum dry the filtered product at a drying temperature of 50° C. for 6 hours to obtain an early strength agent for large temperature difference cementing slurry.

[0067] Example 4

[0068] As a preferred embodiment of the present invention, the early strength agent for large temperature difference cementing slurry disclosed in this embodiment has a specific composition as shown in Table 4.

[0069] Table 4 Example 4 Early Strength Agent Component Table

[0070] Component name Weight parts / parts Nano quartz powder 60 Nano calcined kaolin 32 Dispersants 5 Silane coupling agent 3

[0071] The preparation method of the early strength agent for large temperature difference cementing slurry disclosed in this embodiment is:

[0072] Step 1, weighing 600 parts of anhydrous ethanol and 200 parts of deionized water by mass and mixing them thoroughly to obtain a first mixed solution; weighing 3 parts of a silane coupling agent, adding it to the first mixed solution, and obtaining a second mixed solution after ultrasonic dispersion for 1 hour; adjusting the pH value of the second mixed solution to 4-5 with anhydrous oxalic acid to obtain a third mixed solution, wherein the third mixed solution is a modified solution of nano-quartz powder and nano-calcined kaolin, and transferring the third mixed solution to a reactor equipped with a heating, stirring and condensation reflux device;

[0073] Step 2, weighing 60 parts of nano-quartz powder, 32 parts of nano-calcined kaolin and 5 parts of dispersant by mass and mixing them uniformly to obtain a mixture; and slowly adding the mixture to the third mixed solution to obtain a fourth mixed solution; opening the reflux device in the reactor, heating to 60° C., controlling the stirring speed to 400-500 r / min, reacting the fourth mixed solution for 3 hours, removing the reaction solution, and obtaining a fifth mixed solution;

[0074] Step 3, vacuum filter the fifth mixed liquid, wash the filtered product with anhydrous ethanol, and then vacuum dry the filtered product at a drying temperature of 50° C. for 6 hours to obtain an early strength agent for large temperature difference cementing slurry.

[0075] Comparative Example 1

[0076] The early strength agent of this comparative example adopts a commercially available early strength agent, which is mainly a composite of nano materials and inorganic salt materials.

[0077] Comparative Example 2

[0078] This comparative example is a blank group without adding any early strength agent.

[0079] Test example

[0080] The early strength agents of Examples 1 to 4 were added to cement slurries (density 1.89 g / cm 3 ), the experimental group corresponding to each embodiment was obtained, and the experiment was carried out according to the following formula: Jiahua G-grade oil well cement (based on 100.0wt% of G-grade oil well cement) + 30.0wt% of quartz sand-metakaolin high temperature strength stabilizer + 0.3-0.7wt% early strength agent + 0.30wt% aldehyde ketone condensation polymer dispersant + 0.5wt% AMPS copolymer high temperature retarder (liquid) + 5wt% AMPS-AM high temperature fluid loss reducer (liquid) + 0.2% dimethyl silicone oil defoamer + 70wt% tap water.

[0081] At the same time, comparative example 1 and comparative example 2 (blank group) were set up. Comparative example 1 used a commercially available common early strength agent to replace the early strength agent for large temperature difference cementing slurry of the present invention, and comparative example 2 (blank group) did not add any early strength agent, and the other proportions and conditions were the same as the above configuration.

[0082] According to GB / T19139-2012 Test Method for Oil Well Cement, a large temperature difference cementing slurry was prepared. According to SY / T6544-2017 Performance Requirements for Oil Well Cement Slurry, the engineering properties of comparative example 1, comparative example 2 (blank group) and the large temperature difference cementing slurry in each embodiment were tested. The test method for the 50°C strength at the top of the cement slurry was as follows: the large temperature difference cementing slurry was heated to 150°C, maintained for 30 minutes, shut down, and naturally cooled to 50°C. Then, the thickening experimental slurry cup was taken out, and the thickened oil on the upper layer of the slurry cup was completely removed. The cement slurry was poured into a mold and placed in a 50°C water bath for curing. The curing age was 12h and 24h. The experimental results are shown in Table 5.

[0083] Table 1 Experimental results of examples and control examples

[0084]

[0085] From Table 1 and Figure 3 It can be seen from the results that when no early strength agent is added (Comparative Example 2), under the action of high-temperature retarder, the high-temperature thickening time of the large temperature difference cementing slurry is 322min, and the strength development of the top low-temperature area section at 50°C is very slow, and slow setting or super slow setting occurs, which seriously affects the subsequent construction progress and makes it difficult to ensure the cementing quality of the large temperature difference sealing section.

[0086] From Table 1 and Figure 2 It can be seen that after adding the early strength agent of the prior art (Comparative Example 1), the strength of the low temperature zone section at 50°C at the top of the large temperature difference cementing slurry increased, but the compressive strength of 24h was only 5.7MPa, which still failed to meet the strength requirements for subsequent construction. In addition, after adding the early strength agent of the prior art, the high temperature thickening time of the large temperature difference cementing slurry was significantly shortened, and abnormal gelation occurred, showing that the high temperature curve fluctuated violently and the consistency was inverted, which shows that the early strength agent of the prior art has poor quartz properties in the large temperature difference cementing slurry, and it is difficult to effectively guarantee the cementing quality of the long sealing section.

[0087] From Table 1 and Figure 1 It can be seen that after adding the early strength agent of the present invention (Example 2), the strength of the top low-temperature zone section 50°C of the large temperature difference cementing slurry develops rapidly, and the 24h compressive strength is greater than 12.0MPa. In addition, the early strength agent of the present invention has little effect on the high-temperature thickening time of the large temperature difference cementing slurry, and the thickening time is slightly reduced, but the high-temperature thickening performance is excellent, and no abnormal gelation occurs. In addition, the early strength agent of the present invention has no adverse effect on the working properties of the large temperature difference cementing slurry such as water loss and fluidity, which shows that the early strength agent of the present invention can effectively improve the subsequent construction progress and ensure the cementing quality of the long sealing section of deep wells and ultra-deep wells.

[0088] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.

Claims

1. An early strength agent for large temperature difference cementing slurry, characterized in that: The composition comprises the following components in parts by weight: 40-60 parts of nano quartz powder; 32-45 parts of nano calcined kaolin; Dispersant 5-10 parts; 3 to 5 parts of silane coupling agent.

2. The early strength agent for large temperature difference cementing slurry according to claim 1, characterized in that: The SiO2 content in the nano-quartz powder is ≥ 99.9wt%.

3. The early strength agent for large temperature difference cementing slurry according to claim 1, characterized in that: The particle size of the nano quartz powder ranges from 300 to 400 nm.

4. The early strength agent for large temperature difference cementing slurry according to claim 1, characterized in that: The nano calcined kaolin has a SiO2 content of ≥54wt%, an Al2O3 content of ≥32wt%, and a Fe2O3 content of <3wt%.

5. The early strength agent for large temperature difference cementing slurry according to claim 1, characterized in that: The particle size of the nano calcined kaolin is between 200 and 300 nm.

6. The early strength agent for large temperature difference cementing slurry according to claim 1, characterized in that: The dispersant is a polycarboxylic acid series high-efficiency water reducing agent, and its chemical composition is modified polycarboxylate; the active component in the modified polycarboxylate is ≥90%, and the molecular weight is between 10,000 and 30,000.

7. The early strength agent for large temperature difference cementing slurry according to claim 1, characterized in that: The silane coupling agent is one or more of KH550, KH560, KH570 and KH172.

8. The early strength agent for large temperature difference cementing slurry according to claim 1, characterized in that: The effective component in the silane coupling agent is ≥98%.

9. The method for preparing an early strength agent for large temperature difference cementing slurry according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1, weighing 400-800 parts of anhydrous ethanol and 100-300 parts of deionized water by mass and mixing them thoroughly to obtain a first mixed solution; weighing 3-5 parts of a silane coupling agent, adding it to the first mixed solution, and obtaining a second mixed solution after ultrasonic dispersion for 1 hour; adjusting the pH value of the second mixed solution to 4-5 with anhydrous oxalic acid to obtain a third mixed solution, wherein the third mixed solution is a modified solution of nano-quartz powder and nano-calcined kaolin, and transferring the third mixed solution to a reactor equipped with a heating, stirring and condensing reflux device; preferably, the anhydrous ethanol is 600 parts and the deionized water is 200 parts; Step 2, weighing 40 to 60 parts of nano-quartz powder, 32 to 45 parts of nano-calcined kaolin and 5 to 10 parts of a dispersant by mass and mixing them uniformly to obtain a mixture; and slowly adding the mixture to the third mixed solution to obtain a fourth mixed solution; opening the reflux device in the reactor, heating to 60° C., controlling the stirring speed to 400 to 500 r / min, reacting the fourth mixed solution for 3 hours, removing the reaction solution, and obtaining a fifth mixed solution; Step 3, vacuum filter the fifth mixed liquid, wash the filtered product with anhydrous ethanol, and then vacuum dry the filtered product to obtain an early strength agent for large temperature difference cementing slurry; preferably, the vacuum drying temperature is 50° C. and the drying time is 6 hours.

Citation Information

Patent Citations

  • Low-temperature high-strength tough cement paste and preparation method and application thereof

    CN106986584A

  • Temperature-resistant composite lightweight material low-density well cementation cement

    CN116655299A

  • Low-density early-strength anti-channeling cement paste for ocean well cementation and preparation method thereof

    CN118047571A